Going Bush: International Student Perspectives on Living and Studying at an Australian Rural University Campus - Kathryn Edgeworth; John Eiseman (Journal of Research in Rural Education, 2007)
While there is a signifi cant body of literature concerned with the experience of international students arriving to live and study at urban university campuses, very little of this research addresses the issue of overseas students' transition to rural areas. What issues do international students face when they arrive to live and study in rural places, and how is their experience of university life different from that of their metropolitan counterparts? This paper draws on data from in-depth interviews with non-Englishspeaking-background students from Asia, the Indian Subcontinent, and the Middle East to identify the sorrows and successes of international students arriving to live and study at a small university campus in rural Australia. It explores how place, rurality and diversity work in combination to construct learning and life experiences at a small rural learning institution. It also examines students' connectedness with rural life and meanings, and engages with rurality as a site for educational innovation.